The Early Christians in the Face of Epidemics - Kashchuk, Oleksandr (Studia Ceranea, 2021)
The purpose of the article is to present the reaction of the early Christians to the emergence and the spread of the great epidemics. During the early Christian ages (2nd–3rd centuries) different plagues devastated people of the Roman Empire. Christianity has already prepared some modes of activity to deal with epidemics. These were both ideological and practical means. The main conclusion is that the pestilences during which Christians might show their moral principles, the special manner of life, and activity were one of the reasons to explain conversion to Christianity.